Progression of myopic maculopathy during 18-year follow-up - Fang, Yuxin; Jonas, Jost B. (Ophthalmology, 2018)
Purpose - To examine the progression pattern of myopic maculopathy. - Design - Retrospective, observational case series. - Participants - Highly myopic patients who had been followed up for 10 years or more. Methods - Using fundus photographs, myopic features were differentiated according to Meta-analysis of Pathologic Myopia (META-PM) Study Group recommendations. - Main Outcome Measures - Progression pattern of maculopathy. - Results - The study included 810 eyes of 432 patients (mean age, 42.3±16.8 years; mean axial length, 28.8±1.9 mm; mean follow-up, 18.7±7.1 years). The progression rate of myopic maculopathy was 47.0 per 1000 eye-years. Within the pathologic myopia (PM) group (n = 521 eyes), progression of myopic maculopathy was associated with female gender (odds ratio [OR], 2.21; P = 0.001), older age (OR, 1.03; P = 0.002), longer axial length (OR, 1.20; P = 0.007), greater axial elongation (OR, 1.45; P = 0.005), and development of parapapillary atrophy (PPA; OR, 3.14; P < 0.001). Diffuse atrophy, found in 217 eyes without choroidal neovascularization (CNV) or lacquer cracks (LCs) at baseline, progressed in 111 (51%) eyes, leading to macular diffuse atrophy (n = 64; 64/111 or 58%), patchy atrophy (n = 59; 53%), myopic CNV (n = 18; 16%), LCs (n = 9; 5%), and patchy-related macular atrophy (n = 3; 3%). Patchy atrophy, detected in 63 eyes without CNV or LCs at baseline, showed progression in 60 eyes (95%), leading to enlargement of original patchy atrophy (n = 59; 59/60 or 98%), new patchy atrophy (n = 29; 48%), CNV-related macular atrophy (n = 13; 22%), and patchy-related macular atrophy (n = 5; 8%). Of 66 eyes with LCs, 43 eyes (65%) showed progression with development of new patchy atrophy (n = 38; 38/43 or 88%) and new LCs (n = 7; 16%). Reduction in best-corrected visual acuity (BCVA) was associated mainly (all P < 0.001) with the development of CNV or CNV-related macular atrophy and enlargement of macular atrophy. - Conclusions - The most frequent progression patterns were an extension of peripapillary diffuse atrophy to macular diffuse atrophy in diffuse atrophy, enlargement of the original atrophic lesion in patchy atrophy, and development of patchy atrophy in LCs. Main risk factors for progression were older age, longer axial length, and development of PPA.
Gesehen am 01.10.2020